Tracking and risk of abdominal and general obesity in children between 4 and 9 years of age. The Longitudinal Childhood Obesity Study (ELOIN) - Honorato Ortiz-Marrón; Maira Alejandra Ortiz-Pinto; Gloria Cabañas Pujadas; José Galo Martínez Mosquera; Marien Lorente Miñarro; Francisca Menchero Pinos; María Ordobás Gavín; Iñaki Galán (BMC, 2022)
Abstract Background Studies have shown that overweight and obesity conditions tend to be stable from childhood and adolescence to adulthood. Unfortunately, little is known about the evolution of abdominal obesity during childhood. The aim of this study was to evaluate the temporal variations and risk of general and abdominal obesity between 4, 6, and 9 years of age. Methods Measurements of children in the ELOIN study taken at the three follow-ups of 4, 6, and 9 years of age were included (N = 1,902). Body mass index and waist circumference were recorded via physical examination. General obesity was determined according to the criteria of the World Health Organization (WHO) and abdominal obesity according to the cut-off points proposed by the International Diabetes Federation (IDF). Prevalence ratios (PRs) were estimated by sex and family affluence using generalized estimating equation models and relative risks (RRs) of obesity were obtained via Poisson regression. Results The prevalence of general obesity was 5.1%, 9.1%, and 15.6% at 4, 6, and 9 years, respectively, yielding a PR of 3.05 (95%CI: 2.55-3.60) (9 years old relative to 4 years). The prevalence of abdominal obesity was 6.8%, 8.4%, 14.5% at 4, 6, and 9 years, respectively, and the PR was 2.14 (95%CI: 1.82-2.51) (9 years old relative to 4 years). An inverse correlation was observed between both general and abdominal obesity and socioeconomic status. Among participants with general or abdominal obesity at 4 years of age, 77.3% and 63.6% remained in their obesity classification at 9 years, respectively, and 3.4% and 3.5% presented general or abdominal obesity also at 6 and 9 years of age, respectively. The RRs of general and abdominal obesity at 9 years were 4.61 (95%CI: 2.76-7.72) and 4.14 (95%CI: 2.65-6.48) for children classified with obesity at 4 years of age, increased to 9.36 (95%CI: 7.72-11.35) and 9.56 (95%CI: 7.79-11.74) for children who had obesity at 6 years, and up to 10.27 (95%CI: 8.52-12.37) and 9.88 (95%CI: 8.07-12.11) for children with obesity at both 4 and 6 years, respectively. Conclusions General and abdominal obesity begin at an early age and increase over time, showing an inverse correlation with socioeconomic status. In addition, general and abdominal obesity at 9 years are strongly associated with being classified with obesity at 4 and 6 years, so preventive interventions should be established at very early ages.